Espectroscopia de impedância elétrica do VO2 - Oliveira, João Tiburcio Dias de (2010)
Impedance Spectroscopy has been performed at the metal-semiconductor transition of vanadium dioxide thin films. The samples have been deposited by reactive magnetron sputtering onto heated glass substrates. The crystallographic properties and morphology of the samples have been established by X-ray diffraction. By the spectra measured between 30 and 100 celsius degrees, the volume fractions of the monoclinic and tetragonal phases were quantified. The real and imaginary parts of the electrical impedance have been measured in VO2 thin films as function of the frequency (100 kHz to 1GHz) and temperature (30ºC to 90ºC). For fixed frequencies larger than 100 MHz, the hysteresis presented by the real part of the impedance when the critical temperature is surpassed became inverted. Below the semiconductor/metal transition, the Argand plots can be well reproduced assuming a Debye-like system with one relaxation time. After the beginning of the transition this approach fails, and at least two relaxation times are needed. We attribute one of them to the intrinsic processes taken place in the material, and the other to extrinsic properties like grain boundaries.